Surgical Management of a Large Chronic Prepatellar Bursitis: 2-Stage Technique - Sriskandarasa Senthilkumaran; Steven W. Hamilton (Case Reports in Orthopedics)
Treatment of a large chronic prepatellar bursitis can be difficult to manage surgically because of a high rate of local complications and a significant chance of recurrence. We present a 2-stage technique using negative pressure dressings which produced a good outcome with no recurrence at one year after surgery.